Motives of Poland's Outward Direct Investments from the Lodz Region: Results of a Direct Study - Tomasz Dorożyński; Anetta Kuna-Marszałek; Janusz Świerkocki (Entrepreneurial Business and Economics Review, 2017)
Objective: The objective of the paper is to identify motivation behind FDI followed by enterprises from the Lodz Region and to find out if these motives are similar in companies different in size, share of foreign capital and internationalisation path.